Product Quality as a Determinant of Spa Choice Decisions Amongst Customers in Eldoret Town, Kenya - Koki , Faith K.; Ariya , George; Sempele , Catherine (African Journal of Education,Science and Technology (AJEST), 2021)
The choice decisions individuals make to visit a spa is not current. Over a thousand years ago people sought spas for health and cure through the use of communal baths, to socialize, worship, or relax until when the Greeks and Romans arrived that the art was taken to a higher notch where spas were also used for recreational purposes. There is limited evidence of published research on the determinants of spa choice decisions amongst spa customers in Kenya. Thus, this paper aimed to understand spa-goers’ choice decisions and contemplations in selecting spa amenities. The study sought to assess the influence of product quality on customers’ spa choice decisions. The hypothesis ‘product quality influences customer’s spa choice decisions’ steered the study. Questionnaire was used to collect data. The target population was comprised of 4004 spa customers in Eldoret town. 311 spa customers participated in the study. Descriptive and inferential statistics which included Pearson correlation and regression analysis were employed to examine data collected. The findings indicated that product quality was a very important determinant of customers’ spa choice decisions. A unit change in product quality resulted in 1.088 change in customers’ spa choice decisions. The correlation analysis results also revealed that product quality had a fairly strong positive relationship with customer’s spa choice decisions (r = .768, p-value < .05). The study concluded that product quality influences customers’ spa choice decisions. The study recommended that spa operators should follow up on customers’ product quality contentment and also strive for product consistency. The findings from the research are to benefit the spa operators, policymakers, the public, the private sector, the government, and other stakeholders